Racial and Religious Acceptance Among Students of Higher Learning Institutions in Sabah : A Case Study at Universiti Teknologi MARA Sabah and INTI College / Nazree Dualim - Dualim, Nazree (2010)
According to the history of Malaysia, Malaysia was formed on 16 September 1963 when Singapore, Sabah (North Borneo) and Sarawak agreed to join Federation of Malaya to become one country. However, on 1965 Singapore left the Federation and become an independent state. Malaysia's population comprises many ethnic groups such as Malays, Chinese Indians and Bumiputras that's make Malaysia as multi-racial country which consists of many kind of ethnic group that live together in the same place. In Malaysia, Malays is the major ethnic group followed by Bumiputra of Sabah and Sarawak, Chinese and Indians.